Bidirectional modulation of somatostatin-expressing interneurons in the basolateral amygdala reduces neuropathic pain perception in mice - Apte, Aditya; Fernald, Julia; Slater, Cody; Sorrentino, Marc; Youngerman, Brett; Wang, Qi (Frontiers in Pain Research, 2025)
IntroductionNeuropathic pain is characterized by mechanical allodynia and thermal (heat and cold) hypersensitivity, yet the underlying neural mechanisms remain poorly understood.MethodsUsing chemogenetic excitation and inhibition, we examined the role of inhibitory interneurons in the basolateral amygdala (BLA) in modulating pain perception following nerve injury.ResultsChemogenetic excitation of parvalbumin-positive (PV+) interneurons significantly alleviated mechanical allodynia but had minimal effects on thermal hypersensitivity. However, inhibition of PV+ interneurons did not produce significant changes in pain sensitivity, suggesting that reductions in perisomatic inhibition do not contribute to chronic pain states. In contrast, bidirectional modulation of somatostatin-positive (SST+) interneurons influenced pain perception in a modality-specific manner. Both excitation and inhibition of SST+ interneurons alleviated mechanical allodynia, indicating a potential compensatory role in nociceptive processing. Additionally, SST+ neuron excitation reduced cold hypersensitivity without affecting heat hypersensitivity, whereas inhibition improved heat hypersensitivity but not cold responses.DiscussionOur findings suggest that, in addition to PV+ neurons, SST+ interneurons in the BLA play complex roles in modulating neuropathic pain following nerve injury and may serve as a potential target for future neuromodulation interventions in chronic pain management.